Merging Surface Plasmon Optical Detection with Electronic Sensing - Wolfgang Knoll (Proceedings)
In one of the “classical” configurations of electrolyte-gated field effect transistors (EGOFETs) for biosensing, the planar gate electrode is functionalized by (a monolayer of) receptors, to which the analyte molecules of interest bind from the analyte solution, thereby modifying the gate potential, which in turn modifies the source drain current as the sensor output signal [...]